Dye-doped silica nanoparticle probes for fluorescence lifetime imaging of reductive environments in living cells. Issue 106 (1st November 2016) - Petrizza, Luca; Collot, Mayeul; Richert, Ludovic; Mely, Yves; Prodi, Luca; Klymchenko, Andrey S.
Abstract : Dye-doped silica nanoparticle probes with rationally designed FRET acceptors enable fluorescence lifetime imaging of reductive environments in living cells. Abstract : Fluorescence detection sensitivity can be drastically improved by the application of nanoparticles (NPs) because of their superior brightness compared to organic dyes. Here, using dye-doped silica NPs (SiNPs), we developed FRET-based nanoparticle probes for the detection of reductive environments in living cells. To this end, we designed three FRET acceptors based on black hole quenchers (BHQs). Their polarity was tuned by introducing hydroxyl, PEG and sulfate groups. To conjugate them to NPs, we used an original pre-functionalization approach, where the quencher was coupled by a "click" reaction to Pluronic F127 and further used for the preparation of silica NPs. This approach enabled easy preparation of silica NPs functionalized with varying amounts of quenchers by simple mixing of functionalized and parent Pluronic F127 in different mol%. The increase in the quencher concentration at the SiNPs surface produced a rapid drop in the fluorescence intensity with 80% quenching and a 2-fold drop in the emission lifetime for 16 mol% of the quenchers. Then, to obtain turn-ON sensing of reductive environments, the quenchers were coupled to the NPs through a disulfide linker using the same pre-functionalization strategy. The obtained nano-probes showed a >10-fold increase in their fluorescence in the presence of reductive agents, such as tris(2-carboxyethyl)phosphine (TCEP) and glutathione. Remarkably, BHQ quencher bearing sulfate group showed the highest turn-ON response, probably due to its superior capacity to escape from the NP surface after disulfide bond cleavage. The obtained best nanoprobe was successfully applied for detection of reductive environments inside living cells using fluorescence lifetime imaging (FLIM). This work provides insights for FRET acceptor design and its controlled grafting, which enables preparation of the first redox-sensitive silica nanoparticle probe for lifetime imaging.